2020
DOI: 10.3390/ijms21186733
|View full text |Cite
|
Sign up to set email alerts
|

AGL15 Controls the Embryogenic Reprogramming of Somatic Cells in Arabidopsis through the Histone Acetylation-Mediated Repression of the miRNA Biogenesis Genes

Abstract: The embryogenic transition of somatic cells requires an extensive reprogramming of the cell transcriptome. Relevantly, the extensive modulation of the genes that have a regulatory function, in particular the genes encoding the transcription factors (TFs) and miRNAs, have been indicated as controlling somatic embryogenesis (SE) that is induced in vitro in the somatic cells of plants. Identifying the regulatory relationships between the TFs and miRNAs during SE induction is of central importance for understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 101 publications
0
21
0
Order By: Relevance
“…Finally, it is important to mention a recent study in Arabidopsis [ 68 ] showing that the control of miRNA pathways can be mediated by histone acetylation during the embryogenic reprogramming. This involved the transcription factor AGAMOUS-LIKE 15 (AGL15), which is capable of regulating miR156 both by transcriptional activation of MIR156 or containment of its levels through repression of the miRNA biogenesis genes DCL1 , SERRATE and HEN1 .…”
Section: Induction and Early Somatic Embryogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is important to mention a recent study in Arabidopsis [ 68 ] showing that the control of miRNA pathways can be mediated by histone acetylation during the embryogenic reprogramming. This involved the transcription factor AGAMOUS-LIKE 15 (AGL15), which is capable of regulating miR156 both by transcriptional activation of MIR156 or containment of its levels through repression of the miRNA biogenesis genes DCL1 , SERRATE and HEN1 .…”
Section: Induction and Early Somatic Embryogenesismentioning
confidence: 99%
“…This involved the transcription factor AGAMOUS-LIKE 15 (AGL15), which is capable of regulating miR156 both by transcriptional activation of MIR156 or containment of its levels through repression of the miRNA biogenesis genes DCL1 , SERRATE and HEN1 . In experiments involving the use of an inhibitor of the HDAC histone deacetylases, the authors showed that histone deacetylation is associated with the repression of miRNA processing, and this is mediated by AGL15 [ 68 ].…”
Section: Induction and Early Somatic Embryogenesismentioning
confidence: 99%
“…The ChIP method of Yelagandula et al [ 78 ] with some modifications that were described by Nowak et al [ 71 ] was used. Chromatin was extracted from the cultured explants (~50 mg of tissue) that had been treated with 1% formaldehyde for 20 min on ice under a vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…A LightCycler 480 (Roche, Basel, Switzerland) real-time detection system was used to analyze the relative acetylation level of the WUS -gene-associated chromatin. The qPCR reaction was conducted according to Nowak et al [ 71 ]. The primers that were used in the qPCR were designed using Primer3Plus software (version 3, Molbi, Michelstand, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation